Combined Neurophysiologic and Neuroimaging Approach to Reveal the Structure-Function Paradox in Cervical Myelopathy. (12th October 2021) - Scheuren, Paulina Simonne; David, Gergely; Kramer, John Lawrence Kipling; Jutzeler, Catherine Ruth; Hupp, Markus; Freund, Patrick; Curt, Armin; Hubli, Michèle; Rosner, Jan
Abstract : Background and Objectives: To explore the so-called structure-function paradox in individuals with focal spinal lesions by means of tract-specific MRI coupled with multimodal evoked potentials and quantitative sensory testing. Methods: Individuals with signs and symptoms attributable to cervical myelopathy (i.e., no evidence of competing neurologic diagnoses) were recruited at the Balgrist University Hospital, Zurich, Switzerland, between February 2018 and March 2019. We evaluated the relationship between the extent of structural damage within spinal nociceptive pathways (i.e., dorsal horn, spinothalamic tract, anterior commissure) assessed with atlas-based MRI and (1) the functional integrity of spinal nociceptive pathways measured with contact heat–, cold-, and pinprick-evoked potentials and (2) clinical somatosensory phenotypes assessed with quantitative sensory testing. Results: Sixteen individuals (mean age 61 years) with either degenerative (n = 13) or posttraumatic (n = 3) cervical myelopathy participated in the study. Most individuals presented with mild myelopathy (modified Japanese Orthopaedic Association score >15; n = 13). A total of 71% of individuals presented with structural damage within spinal nociceptive pathways on MRI. However, 50% of these individuals presented with complete functional sparing (i.e., normal contact heat–, cold-, and pinprick-evoked potentials). The extent of structural damage within spinal nociceptive pathways was not associated with functional integrity of thermal (heat: p = 0.57; cold: p = 0.49) and mechano-nociceptive pathways ( p = 0.83) or with the clinical somatosensory phenotype (heat: p = 0.16; cold: p = 0.37; mechanical: p = 0.73). The amount of structural damage to the spinothalamic tract did not correlate with spinothalamic conduction velocity ( p > 0.05; ρ = −0.11). Discussion: Our findings provide neurophysiologic evidence to substantiate that structural damage in the spinal cord does not equate to functional somatosensory deficits. This study recognizes the pronounced structure-function paradox in cervical myelopathies and underlines the inevitable need for a multimodal phenotyping approach to reveal the eloquence of lesions within somatosensory pathways.